The children in child health : negotiating young lives and health in New Zealand - Spray, Julie (Rutgers series in childhood studies, 2020)
Who are the children in child health policy? How do they live and see the world, and why should we know them? A journey into the lives of children coping in a world compromised by poverty and inequality, The Children in Child Health challenges the invisibility of children's perspectives in health policy and argues that paying attention to what children do is critical for understanding the practical and policy implications of these experiences. In the unique context of indigenous Māori and migrant Pacific children in postcolonial New Zealand, Julie Spray explores the intertwining issues of epidemic disease, malnutrition, stress, violence, self-harm, and death to address the problem of how scholars and policy-makers alike can recognize and respond to children as social actors in their health. The Children in Child Health innovatively combines perspectives from childhood studies, medical anthropology, and public health and policy together with evocative ethnography to show how a deep understanding of children's worlds can change our approach to their care.